2020
DOI: 10.1111/peps.12419
|View full text |Cite
|
Sign up to set email alerts
|

Stumbling out of the gate: The energy‐based implications of morning routine disruption

Abstract: Despite academic and practical advice regarding the virtues of daily routines for effective work performance, such routines are vulnerable to disruption from any number of sources. To understand whether and how routine disruptions affect employees at work, we draw on cognitive energetics theory (CET) and explore the potential negative consequences of morning routine disruptions on employees’ energy allocations at work. Moreover, given that CET is fundamentally a theory of goal attainment, we examine the downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 128 publications
(251 reference statements)
1
28
1
Order By: Relevance
“…Specifically, we calculated the value of each path at high (+1 SD) and low (-1 SD) levels of our moderator (Aiken & West, 1991), and used a Monte Carlo simulation with 20,000 replications to construct 95% bias-corrected confidence intervals (CI) around these conditional indirect effects. Similar methods have been used in prior studies (e.g., Foulk et al, 2018;Matta, Scott, Colquitt, Koopman, & Passantino, 2017;McClean et al, 2020;Rosen et al, 2016). Preacher, Rucker, and Hayes (2007) have suggested that moderation, using this method, is supported when the CI for the difference between the two indirect effects (i.e., high and low levels of the moderator) excludes zero.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Specifically, we calculated the value of each path at high (+1 SD) and low (-1 SD) levels of our moderator (Aiken & West, 1991), and used a Monte Carlo simulation with 20,000 replications to construct 95% bias-corrected confidence intervals (CI) around these conditional indirect effects. Similar methods have been used in prior studies (e.g., Foulk et al, 2018;Matta, Scott, Colquitt, Koopman, & Passantino, 2017;McClean et al, 2020;Rosen et al, 2016). Preacher, Rucker, and Hayes (2007) have suggested that moderation, using this method, is supported when the CI for the difference between the two indirect effects (i.e., high and low levels of the moderator) excludes zero.…”
Section: Discussionmentioning
confidence: 93%
“…However, and in order to reduce model complexity and maximize sample size, within-person control variables (i.e., cyclical and lagged variables, daily supervisor positive and negative affect) were modeled with fixed slopes, in line with prior research (e.g., Gabriel et al, 2018;Koopman, Lanaj, & Scott, 2016;McClean, Koopman, Yim, & Klotz, 2020;Rosen et al, 2016). The between-person moderators were modeled at Level 2.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of this pool of self-regulatory resources generally leaves people with a reduced ability to regulate subsequent thoughts, actions and emotions, as they become unwilling to expend further self-regulatory resources (Muraven et al, 2006; Rosen et al, 2016). Thus, initial activities needing self-control tend to leave employees depleted and less able to regulate later activities requiring self-control (McClean et al, in press).…”
Section: Dual Mechanisms Linking Work Intrusions To Job Satisfactionmentioning
confidence: 99%
“…We utilized multilevel path analysis using Mplus 8 (Muthén & Muthén, 2017) to account for the nested nature of our data. Daily FWE, promotion focus, and transformational leadership were modeled at Level 1 with random slopes, while lagged, within-person control variables were modeled with fixed slopes (Koopman et al, 2016; McClean et al, in press; Wang et al, 2013). Our between-person moderators were modeled at Level 2.…”
Section: Discussionmentioning
confidence: 99%